2014
DOI: 10.1017/s1368980014001335
|View full text |Cite
|
Sign up to set email alerts
|

Televised obesity-prevention advertising across US media markets: exposure and content, 2010–2011

Abstract: Objective: To examine levels of exposure and content characteristics for recent televised obesity-prevention campaigns sponsored by state and community health departments, federal agencies, non-profit organizations and television stations in the USA. Design: Nielsen television ratings for obesity-prevention advertising were collected for the top seventy-five US media markets and were used to calculate household exposure levels for 2010 and 2011. Governmental advertisements were coded for content. Setting: Unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 68 publications
1
11
0
6
Order By: Relevance
“…This search process generated 72 ads, representing 39 discrete campaigns aired between 2004 and 2015. Most were dated 2010–2015 ( n =59, 82%), which is consistent with the observation that campaigns relating to obesity prevention were rare prior to the early 2000s 13 …”
Section: Methodssupporting
confidence: 84%
See 1 more Smart Citation
“…This search process generated 72 ads, representing 39 discrete campaigns aired between 2004 and 2015. Most were dated 2010–2015 ( n =59, 82%), which is consistent with the observation that campaigns relating to obesity prevention were rare prior to the early 2000s 13 …”
Section: Methodssupporting
confidence: 84%
“…Most were dated 2010-2015 (n=59, 82%), which is consistent with the observation that campaigns relating to obesity prevention were rare prior to the early 2000s. 13 The ads were initially coded by two authors. Each ad was watched twice and then assessed according to codes reflecting campaign design elements listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…There was a notable lack of alcohol harm reduction ads produced in the United States (US) relative to Australia and the United Kingdom, especially considering that the scale of alcohol-related harm is similar in the US to those countries where most ads were produced [ 1 ]. Even in the absence of national campaigns in the US, it is surprising that there has also been such little activity at the state and community levels, given a recent study found that is where many obesity prevention campaigns originated [ 104 ]. Furthermore, six of the ten ads from the US identified in our study focused on underage drinking—either by demonstrating the harmful effects on youth or encouraging parents to talk to their children about drinking—indicating a need for additional campaign efforts to inform the broader American public of the short- and long-term harms associated with alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…targeted audience rating points) to provide estimates of the frequency of population exposure to certain campaign characteristics (e.g. [ 58 , 104 ]). To examine associations with campaign outcomes, the message characteristics identified in this content analysis could also be used to assist interpretation of the results of population survey or cohort studies of changes in drinking behaviours following exposure to campaign messages with different characteristics [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…for each public service and on TV, there are 400 ads from industry whose share of unhealthy foods is 95%. 178 Another key communicative context is our interpersonal networks of discussion, also referred to as everyday talk. Everyday talk is both formal and informal, has direct consequences on HL practices and the dissemination of information and values, serves to negotiate meaning and labels about health concerns and defines relationships with healthcare providers.…”
Section: A C C E P T E D Mmentioning
confidence: 99%